1
###
If p and q are the roots of the equation x^2 + px + q = 0

If p and q are the roots of the equation x^{2} + px + q = 0, then

- p = 1, q = -2
- p = -2, q = 1
- p = -2, q = 0
- p = 0, q = 1

2
###
If a and b are the roots of the equation x^2 - x + 1 = 0

If a and b are the roots of the equation x^{2} - x + 1 = 0, then a^{2009} + b^{2009} is equal to

- -2
- 2
- -1
- 1

3
###
The equation e^sinx – e^-sinx – 4 = 0 has

The equation e^{sinx} – e^{-sinx} – 4 = 0 has

- Infinite number of real roots
- No real roots
- Exactly one real root
- Exactly four real roots

4
###
Let two numbers have arithmetic mean 9 and geometric mean 4

Let two numbers have arithmetic mean 9 and geometric mean 4. Then these numbers are the roots of the quadratic equation

- x
^{2}+ 18x + 16 = 0 - x
^{2}- 18x - 16 = 0 - x
^{2}- 18x + 16 = 0 - x
^{2}+ 18x - 16 = 0

5
###
A man saves Rs. 200 in each of the first three months of his service

A man saves Rs. 200 in each of the first three months of his service. In each of the subsequent months his saving increases by Rs. 40 more than the saving of immediately previous month. His total saving from the start of service will be Rs. 11040 after

- 18 months
- 19 months
- 20 months
- 21 months

6
###
If α ≠ β but α^2 = 5α - 3 and β^2 = 5β - 3, then the equation having

If α ≠ β but α^{2} = 5α - 3 and β^{2} = 5β - 3, then the equation having α/β and β/α as its roots is

- 3x
^{2}- 19x - 3 = 0 - 3x
^{2}- 19x + 3 = 0 - x
^{2}- 5x + 3 = 0 - 3x
^{2}+ 19x - 3 = 0

7
###
Let a and b be roots of the equation px^2 + qx + r, p ≠ 0

Let a and b be roots of the equation px^{2} + qx + r, p ≠ 0. If p, q, r are in A.P. and 1/a + 1/b = 4, then the value of |a - b| is

- 2√17 / 9
- √61 / 9
- √34 / 9
- 2√13 / 9

8
###
If a, b, c are distinct +ve real numbers and a^2 + b^2 + c^2 = 1

If a, b, c are distinct +ve real numbers and a^{2} + b^{2} + c^{2} = 1, then ab + bc + ca is

- greater than 1
- equal to 1
- less than 1
- any real number

9
###
If (1 – p) is a root of quadratic equation x2 + px + (1 – p) = 0

If (1 – p) is a root of quadratic equation x^{2} + px + (1 – p) = 0, then its roots are

- 0, -1
- 1, 1
- 0, 1
- 2, 1

10
###
What is the sum of the squares of the roots of the equation x^2 + 2x - 143 = 0

What is the sum of the squares of the roots of the equation x^{2} + 2x - 143 = 0?

- 170
- 180
- 190
- 290

11
###
If the difference between the roots of ax^2 + bx + c = 0 is 1

If the difference between the roots of ax^{2} + bx + c = 0 is 1, then which one of the following is correct?

- b
^{2}= a(a + 4c) - a
^{2}= b(b + 4c) - a
^{2}= c(a + 4c) - b
^{2}= a(b + 4c)

12
###
If α and β are the roots of the equation x^2 - q(1+x) - r = 0, then what is (1+α)(1+β)

If α and β are the roots of the equation x^{2} - q(1+x) - r = 0, then what is (1+α)(1+β) equal to?

- 1 - r
- q - r
- 1 + r
- q + r

- In many cases time inconsistency is what prevents our going
- But now we have another group: the unwitting enablers
- The conceptualization of landscape as a geometric object
- Artificial embryo twinning is a relatively low-tech way
- Production and legitimation of scientific knowledge can be approached
- The woodland’s canopy receives most of the sunlight
- Impartiality and objectivity are fiendishly difficult concepts
- The beginning of the universe had, of course, been discussed for a long time